100% Business Rates Retention : Further consultation on the design of the reformed system. A Summary of Responses to the Business Rates Retention Further Consultation.: Further consultation on the design of the reformed system. A Summary of Responses to the Business Rates Retention Further Consultation. (December 2017) - Great Britain., Department for Communities; Local Government
No abstract available